2014
DOI: 10.1089/pho.2013.3557
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Photodynamic Therapy and Sodium Hypochlorite on Monoculture Biofilms of Enterococcus faecalis at Different Stages of Development

Abstract: The bacteria in mature and old biofilms were more resistant to 1% NaOCl than were the bacteria in young biofilms. Overall survival and residual bacteria increase with biofilm aging. PDT and the 2.5% NaOCl solution were equally efficient in completely eliminating E. faecalis biofilms at all three stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Longer incubation times for in vitro biofilm formation have been used more recently. Longer incubation times may result in a thicker biofilm, which may influence its susceptibility to antimicrobial agents [26,27]. However, in what way this could have influenced the results remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Longer incubation times for in vitro biofilm formation have been used more recently. Longer incubation times may result in a thicker biofilm, which may influence its susceptibility to antimicrobial agents [26,27]. However, in what way this could have influenced the results remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Zand et al (23) observed that photodynamic therapy and the 2.5% NaOCL solution were equally efficient in completely eliminating E. faecalis in young, mature and old biofilms using 120 permanent human maxillary and mandibular central incisors. Sabino et al (24) contaminated ten permanent third molar with a bioluminescent strain of C. albicans and introduced into the canals blue methylene and irradiated with laser tip either in contact with pulp chamber or within the canal using an optical diffusion fiber.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the above-mentioned batch-culture studies, phenothiazinium derivatives have also been examined in more applied models: Zand et al (2014) used extracted human maxillary and mandibulary incisors, decoronated them and instrumented their root canals up to #60 K-file. After an autoclavation process Enterococcus faecalis biofilms were formed in these root canals for 4, 6 or 8 weeks.…”
Section: Apdt Against Biofilms In Vitromentioning
confidence: 99%
“…After an autoclavation process Enterococcus faecalis biofilms were formed in these root canals for 4, 6 or 8 weeks. Subsequently, canals were incubated with TBO (25 μg/ml) for 5 min and irradiated with a 625 nm diode laser (100 mW; light dose 214.28 J/cm 2 ) twice for 2.5 min intermitted by a 2.5 min break, applying a total of 2 × 15 J, which led to a complete elimination of Enterococcus faecalis below detection limit of the CFU assay (Zand et al, 2014). …”
Section: Apdt Against Biofilms In Vitromentioning
confidence: 99%